Indirect SPECT Imaging Evaluation for Possible Nose-to-Brain Drug Delivery Using a Compound with Poor Blood-Brain Barrier Permeability in Mice - Asuka Mizutani; Masato Kobayashi; Makoto Ohuchi; Keita Sasaki; Yuka Muranaka; Yusuke Torikai; Shota Fukakusa; Chie Suzuki; Ryuichi Nishii; Shunji Haruta; Yasuhiro Magata; Keiichi Kawai (MDPI AG, 2022)
Single-photon emission computed tomography (SPECT) imaging using intravenous radioactive ligand administration to indirectly evaluate the time-dependent effect of intranasal drugs with poor blood-brain barrier permeability on brain drug distributions in mice was evaluated. The biodistribution was examined using domperidone, a dopamine D2 receptor ligand, as the model drug, with intranasal administration at 0, 15, or 30 min before intravenous [123I]IBZM administration. In the striatum, [123I]IBZM accumulation was significantly lower after intranasal (IN) domperidone administration than in controls 15 min after intravenous [125I]IBZM administration. [123I]IBZM SPECT was acquired with intravenous (IV) or IN domperidone administration 15 min before [123I]IBZM, and time-activity curves were obtained. In the striatum, [123I]IBZM accumulation was clearly lower in the IN group than in the control and IV groups. Time-activity curves showed no significant difference between the control and IV groups in the striatum, and values were significantly lowest during the first 10 min in the IN group. In the IN group, binding potential and % of receptor occupancy were significantly lower and higher, respectively, compared to the control and IV groups. Thus, brain-migrated domperidone inhibited D2R binding of [123I]IBZM. SPECT imaging is suitable for research to indirectly explore nose-to-brain drug delivery and locus-specific biological distribution.